2017
DOI: 10.1017/s0950268817001467
|View full text |Cite
|
Sign up to set email alerts
|

Pandemic-related health behavior: repeat episodes of influenza-like illness related to the 2009 H1N1 influenza pandemic

Abstract: The Houston Health Department (HHD) in Texas tracks influenza-like illness (ILI) in the community through its Influenza Sentinel Surveillance Program, which began in 2008. After the influenza A(H1N1) pandemic (pH1N1) in 2009, investigators sought to assess the feasibility of this program as a non-traditional data source for tracking and monitoring care-seeking activities. Through the process of characterizing and describing patients who had 'return visits', or who were considered the heaviest ILI-related care-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(20 citation statements)
references
References 12 publications
0
20
0
Order By: Relevance
“…This finding should be noticed and worthy of in-depth exploration. As described before, health-seeking behaviors probably increase regarding illnesses with symptoms similar to the pandemic [20][21][22][23]. Several prior studies demonstrated much more health-seeking behaviors and patient visits worldwide under the H1N1 pandemic situation than during non-pandemic periods among individuals with influenza-like symptoms [20][21][22][23].…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…This finding should be noticed and worthy of in-depth exploration. As described before, health-seeking behaviors probably increase regarding illnesses with symptoms similar to the pandemic [20][21][22][23]. Several prior studies demonstrated much more health-seeking behaviors and patient visits worldwide under the H1N1 pandemic situation than during non-pandemic periods among individuals with influenza-like symptoms [20][21][22][23].…”
Section: Discussionmentioning
confidence: 71%
“…As described before, health-seeking behaviors probably increase regarding illnesses with symptoms similar to the pandemic [20][21][22][23]. Several prior studies demonstrated much more health-seeking behaviors and patient visits worldwide under the H1N1 pandemic situation than during non-pandemic periods among individuals with influenza-like symptoms [20][21][22][23]. Meanwhile, an infodemiology study recently found that since coronavirus disease 2019 (COVID-19) has been confirmed as a Public Health Emergency of Concern in 2020, the public awareness of health increased primarily regarding symptoms that similar to those of COVID-19, including influenza, pneumococcal pneumonia, and their vaccines [24].…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Though there are ongoing trials of Bacillus Calmette-Guerin (BCG) vaccine [2] and SARS-CoV-2 mRNA vaccine [3] for use on COVID-19, no vaccine for the prevention of COVID-19 has been approved for public use. Public interest in vaccinations and health-seeking behavior generally increase during outbreaks, particularly with regard to illnesses that manifest with symptoms similar to those of the pandemic [4][5][6][7]. A study in Spain documented a higher volume of phone calls for flu-like symptoms and influenza vaccinations during the flu season and during awareness campaigns [6].…”
Section: Introductionmentioning
confidence: 99%
“…The sentinel provider network was instrumental in monitoring the novel 2009 H1N1 pandemic in Houston [7]. More recently, the ILI data has been used to explore the dynamics of patient health behavior associated with repeat episodes of ILI [8]. However, no attempt has been made thus far to evaluate the forecasting capabilities of existing syndromic surveillance systems (ILINet, hospital EC visit data, and FNY) using Houston’s data.…”
Section: Introductionmentioning
confidence: 99%